Glutamine supplementation in cystic fibrosis: a randomized placebo-controlled trial - Forrester, Doug L.; Knox, Alan J.; Smyth, Alan R.; Barr, Helen L.; Simms, Rebecca; Pacey, Sarah J.; Pavord, Ian D.; Honeybourne, David; Dewar, Jane; Clayton, Andy; Fogarty, Andrew W. (Wiley, 2015)
Rationale: Pulmonary infection and malnutrition in cystic fibrosis are associated with decreased survival. Glutamine has a possible anti-microbial effect, with a specific impact against Pseudomonas aeruginosa. We aimed to test the hypothesis that oral glutamine supplementation (21 g/day) for 8 weeks in adults with cystic fibrosis would decrease pulmonary inflammation and improve clinical status.